Assessment of the Knowledge regarding Ventilator Care Bundle among Final Year BSc. Nursing Students of Mysuru City (International Journal of Nursing Care, 2025)
Background: Ventilator-associated pneumonia (VAP) is nosocomial pneumonia found in 9–27% of patients on mechanically assisted ventilator and is also a major threat to the recovery of patients receiving mechanical ventilation. It usually occurs within 48 h after tracheal intubation. Preventing VAP is one of the important safety issues in critically ill patients receiving mechanical ventilation. Intensive care nurses are in the best position to put the evidence-based guidelines into practice as they are at the patient’s bedside 24 hours a day and therefore, they play an important role in the prevention of VAP. Knowledgeable and skilled nurses are crucial in providing patient care, timely and correct decision minimizes the risks to patient. 1 Prevention and control of ventilator associated pneumonia are dependent on education and awareness of ICU staff towards the problem and on the application of evidence-based strategies.Aim: The aim of the present study was to assess the knowledge regarding ventilator care bundle among Final year BSc. Nursing students of selected nursing colleges at Mysuru cityDesign: Descriptive, non-experimental research designSample and sampling technique: Convenience sampling technique was adopted to select 60 final year BSc nursing students of selected nursing colleges at Mysuru city. Structured Knowledge questionnaire was used to assess the selected personal variables and to assess the knowledge regarding ventilator care bundle among final year BSc nursing students.Results: The study findings revealed that Majority 19(75%) of nursing students got information through health personnels, 05(25%) from electronic mass media and study findings also revealed the findings revealed that majority 41(68.4%) B.SC nursing studentshad average knowledge.Conclusion: Analysis of findings revealed that majority nursing students 50(83.3%) had average knowledge regarding ventilator care bundle. Hence there is need to conduct educational programme to enhance the knowledge and develop desirable attitude regarding Preventing the ventilator associated pneumonia.
Keywords: VAP: ventilator associated pneumonia, VCB: ventilator care bundle.